Determinants of adoption of International Financial Reporting Standards in Ugandan micro finance institutions - Bananuka, Juma; Tumwebaze, Zainabu; Musimenta, Doreen; Nuwagaba, Patience (African Journal of Economic and Management Studies, 2019)
The purpose of this paper is to report on the results of a study carried out to establish the contribution of board of directors’ effectiveness, intellectual capital (IC) and managerial attitude to the adoption of International Financial Reporting Standards (IFRSs) in microfinance institutions (MFIs). Design/methodology/approach – This study is cross-sectional and correlational. Data were collected through a questionnaire survey of 67 MFIs that are members of the Association of Microfinance Institutions of Uganda. The data were analyzed using statistical package for social sciences. Findings – Both board of director’s effectiveness and IC positively and significantly contribute to the adoption of IFRSs. Managerial attitude is positively and significantly associated with the adoption of IFRSs, but its explanatory power is subsumed in IC. Originality/value – To the authors’ knowledge, this is the first study to investigate the contribution of board of director’s effectiveness, IC and managerial attitude to the adoption of IFRSs in MFIs using evidence from a developing African country like Uganda
Keywords: Adoption of IFRSs; Board of director’s effectiveness; Intellectual capital; Managerial attitude; Microfinance institutions; Uganda